Direct drive linear generator designs with aluminium spacer and alternate slot winding for wave energy conversion system - Zamri, N.A.M. (Insight Society, 2017)
This paper presents the study on direct drive linear generator designs with aluminium spacer and alternate slot winding for wave energy conversion system. The study involved the development of permanent magnet linear generator designs with the variation on aluminium spacer utilization as part of the magnet assembly and alternate slot winding usage instead of conventional winding arrangement. The proposed designs were simulated using Finite Element Method (FEM) software to attain the results on flux distribution, air-gap flux density, and open circuit results. The total weight and material cost of each design were also estimated. These results are significant in finding the acceptable design's alternatives to counter the need of huge and heavy linear generator in wave energy converter system. Comparative studies on simulation results and calculated data were conducted between the alternative and conventional design. It is found out that alternate slot winding design improves the performance of conventional design with no impact on design's weight and material cost while aluminium spacer design yields more significant negative results on the performance than the positive effects in term of design's weight and material cost.